Input use and profitability of arable crops production in Nigeria - Awotide, D.O.; Ikudaisi, O.J.; Ajala, S.; Kaltungo, J.H. (Canadian Center of Science and Education, 2015)
The study accessed the profitability of the usage of all input in crop production through Community-Based Agricultural and Rural Development Project (CBARDP) among rural dwellers in the Northern part of the country with the view of comparing the input usage to recommended practices. The study was carried out in five States where the IITA/AfDB-CBARD project was implemented. The States were Adamawa, Bauchi, Gombe, Kaduna and Kwara. Multi-stage sampling technique was used to randomly select 720 farmers for the study for primary data generation. Farmers in study areas cultivated so many crops but the two most important crops (maize and cowpea) were used for the study. The analytical techniques used were descriptive statistics, Gross Margin and Income-Expenditure Ratio. The results showed that maize and cowpea production were profitable in the study area. However, farmers underutilized available production resources with the exception of land input. In addition, farmers did not comply with the recommended agronomic and management practices. The low usage of inputs especially fertilizer would affect the efficiency levels of maize and cowpea farmers implying that farmers were not using the available inputs optimally therefore, effort must be geared towards enhancing input use to promote competitiveness of maize and cowpea production in the area. Finally, since land input was over-utilized, there may be need for farmers to reduce land under cultivation for better utilization of resources.